Analysis of insomnia in those over 60 year of age - Wolińska, Weronika; Pawlak, Iwona Ewa; Mroczek, Bożena (Family Medicine & Primary Care Review, 2016)
Background . Insomnia means an absolute lack of sleep; however, in reality, it is a more complex phenomenon. Insomnia is characterized by an insufficient quantity or quality of sleep. For diagnosis of insomnia, it is crucial to find out about the patient’s subjective feelings. Loneliness is a phenomenon that people experience in an individual way – subjectively. The problems with sleep intensify with age, which can consequently cause depression. Depression is conducive to loneliness, both as a temporary feeling as well as a continual feeling of loneliness and exclusion. Objectives. The aim of this research was to the evaluation of frequency of insomnia among individuals over 60 years of age - students of the University of the Third Age in Stargard. Material and methods . The research was conducted among 131 individuals aged 60 years and over, including 72.51% (n = 95) females and 27.48% (n = 36) males. The mean age was 68.12 ± 6.63. The survey was used with elements of the Athens Insomnia Scale (AIS ), Insomnia Severity Index (ISI ), Beck Depression Inventory and the author’s proprietary questionnaire with socio-economic data. Results . Insomnia was observed among 27.48% (n = 36) of the respondents surveyed with AIS . More than 25% (n = 33) of respondents scored on the borderline for diagnosis of insomnia. The results obtained by combining the Beck Depression Inventory with Athens Insomnia Scale show a statistically significant relationship between insomnia and depression (p = 0.0001). Conclusions . Insomnia is present in more than a quarter of respondents among persons above 60 years of age, being students of the University of the Third Age in Stargard.